Characterizing the sustainability problem in an exhaustible resource model - Tapan Mitra; Geir B. Asheim; Wolfgang Buchholz; Cees Withagen (University of Oslo, Department of Economics, 2012)
The Dasgupta-Heal-Solow-Stiglitz model of capital accumulation and resource depletion poses the following sustainability problem: is it feasible to sustain indefinitely a level of consumption that is bounded away from zero? We provide a complete technological characterization of the sustainability problem in this model without reference to the time path. As a byproduct we show general existence of a maximin optimal path under weaker conditions that those employed in previous work. Our proofs yield new insights into the meaning and significance of Hartwick's reinvestment rule.
Keywords: O10; Q32; 330; Sustainability; Maximin; Erschöpfbare Ressourcen; Ressourcenökonomik; Nachhaltige Entwicklung; Mathematische Optimierung; Theorie